Implementasi Akad Mudharabah Muqayyadah Off Balance Sheet Pada Bank Syariah Indonesia KCP Stabat - Azhar; Augia, Augia Sukma Humaira Amri (Peduli Riset dan Pengabdian Masyarakat, 2022)
One of the Islamic operational principles applied in raising public funds is the mudharabah muqayyadah principle. Mudharabah as a collaboration, but the recording of transactions is done in Off Balance Sheet because the bank does not record it in the Bank's balance sheet, but only records it in the administrative account. Called mudharabah because of the profit sharing scheme, muqayyadah because there are restrictions. This study draws several problems including: how is the implementation of off balance sheet mudharabah muqayyadah contracts at Bank Syariah Indonesia KCP Stabat, how is the risk of financing to customer failure to repay their obligations and the level of health that supports the implementation of off balance sheet mudharabah muqayyadah contracts at Bank Syariah Indonesia KCP Stabat. This research is a field research (field research). The data of this research were obtained from Bank Syariah Indonesia KCP Stabat which became the object of research. Data collection techniques were carried out by observing, interviewing, and enriching with library data. Studying, understanding books, journals, and scholarly writings related to the object of research, the sample was taken as many as 4 people consisting of 4 employees at the bank. Based on the results of the study, that the implementation of off balance sheet mudharabah muqayyadah contracts at Bank Syariah Indonesia KCP Stabat was caused by a lack of funds to open a desired business. By fulfilling the conditions set by Bank Syariah Indonesia KCP Stabat, the bank will first consider whether or not the customer has to borrow the funds. Risk is a threat or action that has an impact on financing.